THE DEVELOPMENT OF METHODOLOGICAL AND ORGANIZATIONAL ASPECTS OF INTERNAL CONTROL OF TAXES AND TAX ACCOUNTING - T. Rogulenko (Вестник университета, 2019)
In article modern methodical and organizational aspects of internal control of taxes at the enterprises of Russia are considered. The factors influencing formation of internal tax control at the enterprises today are revealed and analyzed. On the basis of the carried-out analysis of results of theoretical and practical researches of methodology and the organization of internal control the main aspects necessary for formation of reliable and qualitative system of internal tax control at the enterprises are revealed.